Evaluation of Liver Function Among Patients Presented with Hepatocellular Carcinoma - Shabana Lakho, Dolat Singh, Zaheer Hussain Memon, Sajan Sawai, Nand Lal Seerani, Hira Laghari (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the liver function assessment in the patients presented with hepatocellular carcinoma. Methodology: This cross-sectional study was done at the gastroenterology departments of Liaquat University Hospital Hyderabad and Indus Medical College TM Khan. Patients with an age range of 20 to 70 years, both genders, and having hepatocellular carcinoma were included in the study. A 5 mL blood sample was taken from each participant and sent to the hospital diagnostic laboratory to assess the serum bilirubin level and albumin level. The albumin-bilirubin (ALBI) score was used for hepatic function. Data was collected using a self-made research proforma, and it was analyzed using SPSS 26. Results: A total of 58 cases having HCC were assessed regarding hepatic function. The mean age of the patients was 55.39+12.39 years. Males were in the majority 75.9%, and females were 24.1%. The majority of the patients (72.4%) had child Pugh class C, 12.1% had child Pugh class B, and 15.5% of the cases had child Pugh class A. Elevated bilirubin levels of albumin levels and Alpha-fetoprotein levels were significantly associated to the child Pugh class C (p= <0.05). Most of the cases, 67.3%, had an ALBI score > − 1.39, 10.3% cases had ALBI score − 2.59 to − 1.39, and 22.4% of patients had an ALBI score ≤ − 2.60. Conclusion: Severe hepatic dysfunction was observed to be frequently high among patients having hepatocellular carcinoma, as most of the cases had Pugh class C and ALBI stage 3. Due to the extremely small sample size used in this study, the results are not trustworthy. Keywords: HCC, Hepatic function, Bilirubin, Albumin, ALBI